ANALISA YURIDIS TERHADAP PRAKTEK PERSAINGAN USAHA TIDAK SEHAT DALAM LELANG JASA YANG DILAKUKAN OLEH PT. CHEVRON PACIFIC INDONESIA - Rendra Fitra Adinata; Firdaus '; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Decision of the Business Competition Supervisory Commission, the alleged infringing on a STRONG Namely PT. PT Chevron Pacific Indonesia facilitated. NIS, PT. Avia, PT. Shandy, PT. Jacolin, PT. Freshklindo, and PT. Yogi Pratama Mandiri to review organize the auction winner Dan Indications are horizontal conspiracy BETWEEN PT. NIS, PT. Avia, PT. Shandy, PT. Jacolin, PT. Freshklindo, and PT. Yogi Pratama Mandiri, hearts Form of Agreement for a review determines the winner.The problems of this research there are two: First, how the practice of unfair competition in the auction services performed by PT. Chevron Pacific Indonesia? Second, whether the act of making Letters of Understanding and Statement of Director of PT. NIS categorized fraudulent act or acts of unfair competition are reviewed by Law No. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition ?.The conclusion of this research there are two, namely, first, PT. Chevron Pacific Indonesia as Committee 2008 melaksakan auction or cleaning services / cleaning service meiliki No. 2 packages Package I: 5453-XK and No. Package II: 5454-Xk and of the evaluation was selected the All 6 PT (PT.CPI, PT. NIS , PT. Avia, PT. Shandy, PT. Jacolin, PT. Freshklindo, PT. Yogi). Where they had violated Article 22 of Law No. 5 of 1999 and perform the elements of unfair competition Article 1, item 6 of Law No. 5 of 1999. Second, action is the making of a collective agreement that is carried to the six bidders in within the PT. CPI is an act of unfair competition, it is set in article 4 of Law No. 5 of 1999. And a statement of the director of PT. NIS can not be categorized with cheating, because the contents of the letter it is claimed have capital if PT. NIS is given the opportunity to choose a package auction PT. NIS will choose Package 5454-XK (Tassel-Minas). Suggestions from this study is the first, Better Business Competition Supervisory Commission in implementing some conjecture whether this allegation is a fraudulent act, tort or dishonest act must be clear and have a solid legal basis and surely. Secondly, It should be an improvement in the system of rule of law and persaingaan Invite against unfair business practices, because too much confusion with the interpretation of the elements of unfair competition itself.Keywords: Unfair Competition-Auction Services-PT. Chevron Pacific Indonesia